For lines to be perpendicular, the slope of one of them must be the inverse negative of the other one. So for example given the lines:
![y=mx+b](https://img.qammunity.org/2023/formulas/mathematics/high-school/smsb8cbft03lwblmi49nf2l6jby2ofxzws.png)
![y=nx+c](https://img.qammunity.org/2023/formulas/mathematics/college/lzt0gdx94tz6lilm11urm1978ne5azn45y.png)
For them to be perpendicular their slopes must be:
![n=-(1)/(m)](https://img.qammunity.org/2023/formulas/mathematics/college/n5nhf1y0xcdz1d272tpuijq6tp0l5nj7ld.png)
To determine the equation of a line perpendicular to the given one, the first step is to calculate the slope of the graphed line.
Using two points of the line, for example: (0,3) and (4,6)
![\begin{gathered} m=(y_1-y_2)/(x_1-x_2) \\ m=(6-3)/(4-0)=(3)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dozage1aotazue7tm209nxff9qmhxg8gaf.png)
The slope of the graphed line is
![m=(3)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/116i3gocb9gnf3xnfj6g4q4modafl2k2gl.png)
Now the slope of the perpendicular line must be the inverse negative so that:
![\begin{gathered} n=-(1)/(m) \\ n=-(4)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7xvdxrjlsnt3anjs65z1z2duj5ywv02r1a.png)
Now that we know the slope of the perpendicular line, and is given that it crosses the point (3,-1) we can use the point slope form to determine its equation
![y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csobd57zth7rh9k4hz9amldzpq2owf0z4j.png)
For our line
![\begin{gathered} y-(-1)=-(4)/(3)(x-3) \\ y+1=-(4)/(3)x+4 \\ y=-(4)/(3)x+4-1 \\ y=-(4)/(3)x+3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/utojbsx5fp7bjztvbs0esuszt2v06b4tvy.png)
The equation of a perpendicular line of the one shown in the graph rthat goes through point (3,-1) is
![y=-(4)/(3)x+3](https://img.qammunity.org/2023/formulas/mathematics/college/avk2sleqiurck75sjvrauxhk8e5t77pp4x.png)